Perbandingan Penyelesaian Perselisihan Hubungan Industrial Melalui Konsilisasi Dan Mediasi Di Departemen Tenaga Kerja Daerah Istimewa Yogyakarta - Rezaldi, Muhammad; Paryadi (Faculty of Law, University of Mataram, 2024)
The aim of this research is to determine and analyze the number of industrial relations disputes resolved through conciliation and mediation in 2021 at the Department of Labor of the Special Region of Yogyakarta and to determine and analyze the factors that lead to the resolution of industrial relations disputes at the Department of Labor of the Special Region of Yogyakarta through conciliation is used less often than mediation. Types of juridical research. Data sources use primary and secondary data. Data collection techniques used interviews and literature study. Data analysis techniques are descriptive qualitative. The results of the research show that the industrial relations disputes handled by mediators at the Manpower and Transmigration Service of the Special Region of Yogyakarta most often involve disputes regarding termination of employment. The only industrial relations disputes handled by mediators at the Yogyakarta Special Region Manpower and Transmigration Service which must continue the dispute to the Industrial Relations Court are cases of employment termination. Factors that cause the resolution of industrial relations disputes at the Yogyakarta Special Region Manpower and Transmigration Service include industrial relations mediation being considered more effective than conciliation, the absence of conciliators at the Yogyakarta Special Region Manpower and Transmigration Service since March 2020 due to death, differences authority between mediators and conciliators in terms of handling types of industrial relations problems and mediation has advantages over conciliation.